The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/pedi.12872
|View full text |Cite
|
Sign up to set email alerts
|

Reduced burden of diabetes and improved quality of life: Experiences from unrestricted day‐and‐night hybrid closed‐loop use in very young children with type 1 diabetes

Abstract: Objective To evaluate the experiences of families with very young children aged 1 to 7 years (inclusive) with type 1 diabetes using day‐and‐night hybrid closed‐loop insulin delivery. Methods Parents/caregivers of 20 children aged 1 to 7 years with type 1 diabetes completed a closed‐loop experience survey following two 3‐week periods of unrestricted day‐and‐night hybrid closed‐loop insulin therapy using Cambridge FlorenceM system at home. Benefits, limitations, and improvements of closed‐loop technology were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 9 publications
5
61
0
2
Order By: Relevance
“…Furthermore, it has been shown that the use of CGM systems 9 might be a main driver of improvement in terms of glycemic control and that the method of insulin delivery (pen vs. CSII) might be of lesser importance in all age groups 10,11 . As part of a future development, for the implementation of hybrid closed‐loop systems, both compartments – sensor and pump are a must 12 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that the use of CGM systems 9 might be a main driver of improvement in terms of glycemic control and that the method of insulin delivery (pen vs. CSII) might be of lesser importance in all age groups 10,11 . As part of a future development, for the implementation of hybrid closed‐loop systems, both compartments – sensor and pump are a must 12 …”
Section: Introductionmentioning
confidence: 99%
“…A multicenter trial with 20 very young children between 1 and 7 years of age using an experimental closed loop system containing a modified Medtronic ™ 640G insulin pump (investigational use only; Medtronic, Northridge, California), a real‐time continuous glucose sensor (Enlite 3, Medtronic), and the FlorenceM CL system control algorithm version 0.3.46 reported similar results. Responders especially emphasized the improvement in quality of sleep with CL for both caregivers and users [ 32 ]. We could reproduce these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The Omnipod Horizon system [124] uses a patch pump and both its safety and efficacy were demonstrated in both adults and pediatric T1Ds even also in an outpatient setting [125,126]. CLCs equally allow a better QoL, by reducing the burden related to diabetes by demonstrating a significant reduction of the time spent in diabetes management [127,128]. These results need to be confirmed in real life since the effectiveness of clinical trials in selected subjects could have impacted the results.…”
Section: Artificial Pancreasmentioning
confidence: 99%